Studi Pengelolaan Sampah Masyarakat di Komplek Perumahan CempakaPermai Kecamatan Gading Cempaka Kota Bengkulu - Priyanto, Gusti; Zairin; Yunita, Mirna (Jurnal Georafflesia : Artikel Ilmiah Pendidikan Geografi, 2025)
This study aims to describe the condition of household waste management, the influencing factors, and the roles of relevant stakeholders. This research uses a qualitative descriptive approach. Data were collected through direct observation, in-depth interviews with 25 key informants consisting of residents, neighborhood heads, sanitation workers, and environmental organizations, and supported by field documentation. The results show that waste management in the study area is still conventional and unstructured. Most residents do not separate organic and inorganic waste, supporting facilities such as waste sorting bins and official temporary disposal sites (TPS) are not available, and education or outreach programs from local authorities are still minimal. Public awareness remains low, and the responsibility for waste management largely rests with sanitation workers. This study recommends strengthening outreach programs, providing adequate waste sorting facilities, and establishing waste banks to encourage active community participation. The findings are expected to serve as a reference for stakeholders in formulating effective and sustainable community-based waste management policies.